Vocational Counseling for Students at Trade Schools - Bùi, Văn Hưng (Journal of Technical Education Science, 2010)
Vocational counseling for the young is attracting more and more attention of the society. Although not really a new field, vocational counseling has not become a systematic field of research in Vietnam. Neither has it got any expert training program so far. Even the terminology and its connotations should be defined and made consistent with the context of Vietnam. On the other hand, this is a highly interdisciplinary field requiring trained professionals with actual practice in specific situations. This article wants to introduce a “primary field” in vocational counseling with its specific objects and methods, specific tools, namely career counseling for students of vocational schools.